The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Stability of Vaccines - N. Dumpa; K. Goel; Yuhan Guo; H. McFall; Amit Raviraj Pillai; Ashay Shukla; M. A. Repka; S. Narasimha Murthy (AAPS PharmSciTech, 2019)

Taming the symbiont for coexistence: a host PGRP neutralizes a bacterial symbiont toxin - Joshua V. Troll; Eric H. Bent; Nicholas Pacquette; Andrew M. Wier; William E. Goldman; Neal Silverman; Margaret J. McFall‐Ngai (Environmental Microbiology, 2010)
Summary In horizontally transmitted mutualisms between marine animals and their bacterial partners, the host environment promotes the initial colonization by specific symbionts that it harvests from the surrounding bacterioplankton. Subsequently, the host must develop long‐term tolerance to immunogenic bacterial molecules, such as peptidoglycan and lipopolysaccaride derivatives. We describe the characterization of the activity of a host peptidoglycan recognition protein (EsPGRP2) during establishment of the symbiosis between the squid Euprymna scolopes and its luminous bacterial symbiont Vibrio fischeri . Using confocal immunocytochemistry, we localized EsPGRP2 to all epithelial surfaces of the animal, and determined that it is exported in association with mucus shedding. Most notably, EsPGRP2 was released by the crypt epithelia into the extracellular spaces housing the symbionts. This translocation occurred only after the symbionts had triggered host morphogenesis, a process that is induced by exposure to the peptidoglycan monomer tracheal cytotoxin (TCT), a bacterial ‘toxin’ that is constitutively exported by V. fischeri . Enzymatic analyses demonstrated that, like many described PGRPs, EsPGRP2 has a TCT‐degrading amidase activity. The timing of EsPGRP2 export into the crypts provides evidence that the host does not export this protein until after TCT induces morphogenesis, and thereafter EsPGRP2 is constantly present in the crypts ameliorating the effects of V. fischeri TCT.